The impact of COVID-19 pandemic on mental burden and quality of life in physicians: results of an online survey - Wetzel, Lea; Halfmann, Marie; Castioni, Noah; Kiefer, Falk; König, Sarah; Schmieder, Astrid; Koopmann, Anne (Frontiers in psychiatry, 2023)
Background: In previous pan-/epidemics such as the SARS epidemic of 2002/2003, negative effects on the wellbeing and an increase in symptoms of depression and anxiety were observed in doctors due to social isolation and the threat they experienced. Therefore, it is feared that the COVID-19 pandemic will also have a negative impact on the mental health and quality of life of doctors. Objective: The impact of the COVID-19 pandemic on the mental health of physicians. In particular, on the subjective anxiety and burden, depression and quality of life for the total sample and subsamples (work in COVID-19 units vs. no work in COVID-19 units). Materials and methods: In an online survey, 107 physicians (23-42 years) were asked about their mental health during the COVID-19 pandemic. In addition to socio-demographic data, pandemic- and work-related data were also included. For example, infection control measures, deployment on COVID-19 wards and the subjective perceived threat posed by the pandemic. The physicians were asked to rate their perceived anxiety and stress, retrospectively, at 7 different points in time during the pandemic. The Hospital Anxiety and Depression Scale (HADS) was used to retrospectively assess symptoms of anxiety and depression before and after the onset of the pandemic. The quality of life of the participants after 2 years of the pandemic was assessed using the WHO Quality of Life (WHOQOL-BREF). Results: Both subjective anxiety and burden showed wave-like patterns with higher scores in autumn, winter and spring. We observed significant differences between the seven measurement time points for anxiety as well as for burden. Symptoms of depression and anxiety increased significantly during the COVID-19 pandemic compared to the pre-pandemic time. Physicians who worked at COVID-19 units showed higher scores in quality of life related to social relationships than physicians not working at COVID-19 units. The multi-factorial ANOVA showed that previous psychiatric illness, greater difference in depression scores, higher anxiety scores and less work experience led to lower quality of life. Conclusion: Hospitals should offer specific support, such as supervision, to prevent the development of longer-term psychiatric sequelae likely to lead to sick leave and high costs for the healthcare system. Trial registration: The study has been registered at the German Clinical Trials Registry (DRKS-ID: DRKS00028984).